1993
DOI: 10.1017/s0950268800050937
|View full text |Cite
|
Sign up to set email alerts
|

Factors enhancing adherence of toxigenicStaphylococcus aureusto epithelial cells and their possible role in sudden infant death syndrome

Abstract: SUMMARYToxigenic strains of Staphylococcus aureus have been suggested to play a role in sudden infant death syndrome (SIDS). In this study we examined two factors that might enhance binding of toxigenic staphylococci to epithelial cells of infants in the age range in which cot deaths are prevalent: expression of the Lewisa antigen and infection with respiratory syncytial virus (RSVT). By flow cytometry we demonstrated that binding of three toxigenic strains of S. aureus to cells from nonsecretors was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 39 publications
5
74
0
1
Order By: Relevance
“…In addition, a viral infection can be associated with a rise in antipseudomonal antibodies in CF patients with intermittent or chronic pseudomonal colonization, especially in case of RSV infection (14). These findings are furthermore consistent with several studies that demonstrate enhanced adherence of bacteria, like Haemophilus influenzae and Staphylococcus aureus, to epithelial cells after viral infection in vitro (9,18,19) and in vivo (20,21). However, there are only few experimental data about synergism between viruses and P. aeruginosa in inducing infections.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, a viral infection can be associated with a rise in antipseudomonal antibodies in CF patients with intermittent or chronic pseudomonal colonization, especially in case of RSV infection (14). These findings are furthermore consistent with several studies that demonstrate enhanced adherence of bacteria, like Haemophilus influenzae and Staphylococcus aureus, to epithelial cells after viral infection in vitro (9,18,19) and in vivo (20,21). However, there are only few experimental data about synergism between viruses and P. aeruginosa in inducing infections.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the high incidence of bacterial and RSV co-infection in both children and adults, only few studies aimed to investigate the possible interactions between S. aureus and this virus [8790]. RSV is supposed to exacerbate S. aureus co-infection via at least two mechanisms: enhancing the adhesion of S. aureus to the RSV-infected cells [88,89], and decreasing the bacterial clearance by altering the immune response to S. aureus [87,90]. …”
Section: Mechanisms Involved In Interactions Between Staphylococcus Amentioning
confidence: 99%
“…In vitro studies had shown that RSV-infected epithelial cells bind more S. aureus than uninfected cells [88,89]. Study of nasal washings in patients with respiratory virus diseases has shown that secretion of Lewis blood group antigens is associated with RSV infection [91].…”
Section: Mechanisms Involved In Interactions Between Staphylococcus Amentioning
confidence: 99%
See 2 more Smart Citations